Effectiveness of Global Posture Re-education and McKenzie technique in Non-Specific Low Back Pain - Senthil, Selvam P.; Vinodhini, R; Vinosh Kumar, Purushothaman; Ambusam, Subramaniam; Rajkumar Krishnan, Vasanthi (INTI International University, 2022)
Low back pain is a highly prevalent and disabling condition worldwide. Despite plenty of research having been conducted among those with non-specific low back pain, there is still a scarcity of research in the application of McKenzie, especially in the primary medical care phase. Besides, the evidence on the effectiveness of intervention in patients with persistent nonspecific low back pain is conflicting because of the significant risk of bias among studies. Thus, the current study was conducted to examine the effectiveness of global postural re-education and the McKenzie technique in patients with non-specific low back pain. The current experimental study was conducted among 30 patients with persistent non-specific low back pain. Participants were randomly divided into two groups (Group A: Mckenzie and global postural education and Group B: Mckenzie only). At the baseline, pain, lumbar-pelvic flexibility, and disability score were taken using the Visual Analogue Scale, modified finger-to-floor test, and Owstery Disability Index, respectively. The intervention was conducted for three weeks. The results were analysed using the descriptive statistics and paired t-test. All the variables showed a high mean value in the post-test when compared to the pre-test values in both Group A and Group B. However, in comparison between pre and post three weeks intervention, Group A showed a significant difference. In conclusion, the current study suggests that the combination of global postural education and McKenzie is more useful and efficient than McKenzie alone among patients with non-specific low back pain.